AUTOMATIC FIXING OF VIOLATIONS OF THE RULES OF TRAFFIC OF UKRAINE - Garkusha Вячеслав Викторович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The scientific article is devoted to the mechanism of bringing to administrative responsibility for violation of traffic rules, fixed with operating in automatic mode, the technical means having the function of photography, video shooting.